Maternal and Neonatal Outcomes After Planned or Emergency Delivery for Placenta Accreta Spectrum: A Systematic Review and Meta-Analysis - Zhong, Wei; Zhu, Fang; Li, Shengqiong; Chen, Jin; He, Fengya; Xin, Jie; Yang, Mei (Frontiers in Medicine, 2021)
Objective: To compare maternal and neonatal outcomes for women with placenta accreta syndrome (PAS) delivering via a planned or emergent approach. Methods: A systematic search for relevant studies was conducted by screening the PubMed, Scopus, Web of Science, and Google Scholar electronic databases. Included studies should have been retrospective record-based or prospective in design. They must have compared maternal and/or neonatal outcomes for PAS patients delivering via planned and emergency procedures. Strength of association was presented as pooled adjusted relative risk (RR) for categorical outcomes and weighted mean difference (WMD) for continuous outcomes. Statistical analysis was done using STATA version 16.0. Results: Nine articles were included in the meta-analysis. PAS patients undergoing planned deliveries had increased gestational ages, required fewer units of transfused blood, experienced shorter hospital stay durations, and presented reduced risks for maternal ICU admission and severe maternal morbidity. Neonates born to mothers undergoing planned deliveries had increased birth weights and decreased NICU admission risk. Conclusion: These findings indicate a planned approach for delivery is better for maternal and neonatal outcomes compared to urgent/emergency delivery for PAS patients.